Hodgkin's disease occurring in primary Sjögren's syndrome. Issue 8 (August 1990) - Martín-Santos, J M; Carretero, L; Armentia, A; Alonso, E; Gil, I
Abstract : A 57 year old woman with a 13 year history of mouth dryness, keratoconjunctivitis sicca, and recurrent bronchial infections presented with multiple lymphadenopathies. Histological diagnosis was Hodgkin's disease. B and T cell lymphomas are well known complications of Sjögren's syndrome. This case provides evidence that Hodgkin's disease may also be associated with this syndrome.